Pendidikan Seni sebagai Alat Pelestarian dan Pengembangan Budaya Batik di SMK Negeri 4 Palangka Raya - Ni Wayan Ratih Wahyuriani; I Wayan Karja; Ida Ayu Trisnawati (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Art education plays a crucial role in preserving and developing local cultural heritage, including batik. This study aims to examine the role of art education at SMK Negeri 4 Palangkaraya in supporting the preservation and development of batik culture. The focus of the study was on the learning process in the Batik and Textile Creative Crafts Program, specifically for eleventh-grade students. This study employed a qualitative approach with case study and descriptive methods. Data collection techniques included analysis of learning documents, in-depth interviews with teachers and students, and direct observation of learning and practical activities. The results indicate that the art learning process at this school focuses not only on technical skills in batik but also integrates rich cultural content, such as the history of batik, the philosophical values within motifs, and the role of batik in local cultural identity. Through this approach, students are equipped not only with technical skills but also with a deep understanding of the cultural values inherent in batik. Furthermore, student involvement in hands-on activities and community-based projects provides space for innovation. They are encouraged to create contemporary batik designs that remain rooted in traditional motifs but are adapted to contemporary tastes. This activity also fosters a sense of ownership of cultural heritage and fosters creativity and independence. Thus, arts education at SMK Negeri 4 Palangkaraya has proven to play a strategic role in maintaining the sustainability of batik culture. More than just skills training, arts education is an effective means of building cultural awareness, fostering innovation, and strengthening local identity among the younger generation.